A Literature-based Aproach for Eleventh Novice Learners: A Way to Incorporate Literary Texts in Costa Rica Public High Schools - Altamirano Alvarado, Jorge (Escuela de Lenguas Modernas, Universidad de Costa Rica, 2017)
n this article, we developed a literature-based approach aimed at eleventh graders from public high schools. The methodological approach centers on developing short stories as a way to incorporate literary texts as part of the English Syllabus as well as to determine the students’ level of comprehension. In addition, this literature-based approach intends to encourage students to do both modeled and shared reading. En este artículo, desarrollamos un enfoque metodológico para la ense- ñanza de la literatura a estudiantes de undécimo nivel en un colegio del sistema público. La metodología del enfoque se centra en utilizar el cuento como texto literario e incorporar así la literatura como parte del currículum con el propósito de determinar el nivel de comprensión de los estudiantes. Además, el enfoque metodológico literario tiene la intención de ofrecer al estudiantado una lectura modelada y compartida.